Multimodal Communication óf Specialized Knowledge across Hypertext Innovation and Generic Tradition - Maier, Carmen Daniela (HERMES - Journal of Language and Communication in Business, 2008)
As more and more educators try to employ interactive texts in the educational process, investigation of how knowledge communication takes place in hypertext becomes increasingly signiﬁ cant. Drawing on a multimodal theoretical framework, this paper explores knowledge communication in interactive texts from the Volcano World website (http://volcano.und.edu/vwdocs/Online/index.html). The analytical focus is ﬁrst on how specialized knowledge is multimodally constructed inside the generic framework of traditional lessons through different types of interactive exchanges and across several semiotic modes. Second, the analysis discusses how the linear reading path imposed by the generic structure of traditional lessons is disrupted by hypertext’s meaning-making pathways. The paper concludes that the stable generic structure of lessons combined with the openness of hyperlinks can be and, to some extent, is being exploited in websites like Volcano World to enhance the process of progressively acquiring, producing and exchanging specialized knowledge across several semiotic modes. By detecting the kind of meaning-making structures that can be established when communicating specialized knowledge in a hypertext environment, educators can continuously adapt online interactive texts to accommodate students accustomed to complex interactive activities and eager to get to grips with them.